Study of Consistent Characteristics of the Ointment with Octopirox - V. A. Solodovnyk; V. V. Hladyshev; A. P. Lysianska (Zaporozhye State Medical University, 2019)
Effective therapy of seborrheic dermatitis remains an actual task for the dermatological practice. Octopirox has a significant antimycotic activity and a wide spectrum of antibacterial effect both against gram-negative and gram-positive pathogenic microorganisms. On a base of the complex physical-chemical, pharmaco-technological and biopharmaceutical investigations the compositions of applicative dosage forms with octopirox and for external use with octopirox and deresined naphthalene for therapy and prophylaxis of seborrheic dermatitis were developed by the department of technology of medications at Zaporizhzhia State Medical University. The aim of this work is assessment of the consistent properties of the developed ointment compositions with octopirox and refined naphthalene to determine the optimal composition of the combined soft dosage form based on the results of rheological study. Materials and methods. As the objects of the study the ointments on the base of sodium carboxymethylcellulose and methylcellulose glycerogels, which provide optimal octopyrox releasing from these hydrophilic delivery vehicles were used. Results. Establishment of dependence of the effective viscosity value from the shear speed for the experimental ointments with octopirox and refined naphthalene revealed that the deformation speed decreases with rising of tangential shear stress, and viscosity of compositions decreases. This is an evidence of structure in studying systems. Obtained results allow to predict the ointment composition with octopirox and refined naphthalene on the base of sodium carboxymethylcellulose glycerogel as more perspective for the further study. Conclusions. It was revealed that consistent characteristics of the ointment composition on the base of sodium carboxymethylcellulose delivery vehicle are practically completely situated within the limits of rheologic optimum of consistency for ointments, and "mechanical stability" value (2.37) characterizes the system as exceptionally thixotropic providing system recoverability after loading and allows to predict the stability of rheologic characteristics during long term of storage. Location of the rheogram of ointment with octopirox and refined naphthalene on the base of methylcellulose glycerogel practically out the limits of rheologic optimum of consistency for ointments indicates an inexpediency of further study of this applicative system for the topical administration. Calculated factors of dynamic flow of composition on the sodium carboxymethylcellulose delivery vehicle show positive spreading extent during application on the skin or during technologic operations of manufacturing.